Warren G. Harding papers - Harding, Warren G. (Warren Gamaliel), 1865-1923.
Correspondence, speeches, subject files, scrapbook, and other papers relating in part to Armistice Day, the De Ronde sugar claim, and political campaigns. Correspondents include Harry S. New and Carolyn Harding Votaw.
In part, negative photocopies.
President of the United States.
Collection material in English.
Keywords: New, Harry S. -- 1858-1937 -- Correspondence; Votaw, Carolyn Harding -- Correspondence; Armistice Day; Elections -- United States; Sugar trade; United States -- Politics and government -- 1921-1923.; Presidents -- United States